Avaliação de investimento para aquisição de veículo de transporte de cargas - Semaenski, Cristiano Junior (2023)
The present article deals with an analysis of the feasibility of acquiring a vehicle for cargo transportation, in which two partners identified a business opportunity and are seeking a study to assess the feasibility of acquiring a new Volkswagen truck transports dairy products from the producer to dairy companies. The partners already have an income and see this investment as a second source of revenue, so it is important to evaluate the economic and financial feasibility as well as the associated costs. The research will be conducted in the form of a proposal for plans, with data collection through interviews to gather information for investment evaluation. Thus, the net present value (NPV), internal rate of return (IRR), and payback were calculated in two possible scenarios. In the first scenario, considering a 5-year financing period, the NPV was negative at R$ 31,123.13, closing the period with an IRR of only 2.66%, making it unattractive. In the second scenario, the investment becomes viable when considering the residual value and the sale of assets, resulting in a positive NPV of R$ 218,605.94 and an IRR of 45.76%, making it attractive. Therefore, the partners decided not to proceed with the investment due to the associated risks and because the main idea is to make a viable and profitable investment. Thus, the present study achieved the expected objective